The heritability of history: how inherited status affects cooperative behaviour in public goods games - Kreft, Brynde (School of Economics, 2020)
The intergenerational transmission of inequality causes individuals to receive unearned advantages and disadvantages in society. Understanding how the transmission of unearned material status affects social interactions will help to illuminate how the relationship between material status and social connections affects an individual’s overall welfare. The behavioural responses to intergenerational inequality have proven difficult to isolate in observational data. In a series of laboratory experiments, an inherited inequality framing was shown to cause significantly different public good game contribution behaviour for various types of individual. While inheritance status improved cooperation among those who inherited a high status in groups with only others who inherited high endowments, the inheritance frame is associated with reduced cooperation in unequal groups and in groups comprised of exclusively inheritors of low material status. The inheritance frame established a powerful historical context for participants, the reduction in cooperation caused by inherited inequality persisted even after redistribution interventions which eliminated the material inequality.